STOCK MARKET AMIDST THE COVID-19 PANDEMIC: A BIBLIOMETRIC STUDY - Mudita Lau; Maria Widyarini; Achmad Faisal (Business Administration Department - Universitas Katolik Parahyangan, 2022)
COVID-19 was declared a pandemic in March 2020 and wreaked havoc on the economy and business, including the stock market. This disruption has led various researchers to publish about the effects of the COVID-19 pandemic on the stock market. Due to the massive number of publications, this study reviews this novel research topic using bibliometric analysis. This study aims to identify thematic clusters, collaboration networks, and high-impact publications and research constituents. This study utilizes science mapping and performance analysis techniques such as co-authorship, bibliographic coupling, and citation analysis. This study merges data from Scopus and Dimensions database with R Studio bibliometrix package, which then are plotted using VOS Viewer and biblioshiny. The findings of this study are collaboration networks, thematic clusters, and a list of high-impact publications and research constituents. This study’s contribution is the intellectual and bibliometric structure of the COVID-19 and stock market research field. Based on these study, COVID-19 does not only affect the stock market negatively but also reveal the connectedness between the stock market and commodities.